1976
DOI: 10.1139/z76-232
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes during the growth cycle of axenic and monoxenic Tetrahymena pyriformis

Abstract: Morphometric data were collected from Tetrahymena pyriformis (WH-14, syngen I, mating type II) grown in two different media, one axenic and one monoxenic (with Serratia marcescens), at various times during the growth cycle. Stationary phase cells differed morphometrically from exponential phase cells in different ways in the two media. It is proposed that, in the monoxenic medium, division stopped because the food resource was depleted, while in the axenic medium division was blocked before food limitation occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…1). A number of authors have shown similar high correlations between biovolume and biomass for the algae Euglena [8], Selenastrum and Chlorella [37], and protozoa Tetrahymena [4,32] and Colpidium [31 ]. Drake and Tsuchiya [11 ] established the accuracy of electronic techniques for counting mixed populations of microorganisms and applied their procedures to differential counting of mixed cultures of bacteria and protozoa, bacteria and yeast, and large and small bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…1). A number of authors have shown similar high correlations between biovolume and biomass for the algae Euglena [8], Selenastrum and Chlorella [37], and protozoa Tetrahymena [4,32] and Colpidium [31 ]. Drake and Tsuchiya [11 ] established the accuracy of electronic techniques for counting mixed populations of microorganisms and applied their procedures to differential counting of mixed cultures of bacteria and protozoa, bacteria and yeast, and large and small bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…This seven‐days period ensures that genotypes all reached the stationary phase of their logistic growth. The normalization of measurements at the same phase is important because the morphology of cells changes along the growth cycle in axenic Tetrahymena cultures (Taylor et al 1976). The ‘after' measurement was used to quantify traits at the exact time of dispersal.…”
Section: Methodsmentioning
confidence: 99%
“…The possibility always exists that under different culture conditions higher growth rates could be attained. This error is magnified by r/L because ciliates in balanced growth at less than their maximal rate are smaller than when they are growing more rapidly (Curds and Cockburn, 1971 ;Taylor et al, 1976). The bacterial species used as food in this study, A. aerogenes, has been widely used as a food for ciliates with few reported cases of toxicity.…”
Section: The Reliability Of the Maximum Growth Rate Estimatesmentioning
confidence: 99%